Konsep Keadilan Sosial dalam Perspektif Al-Qur’an - Indira Ramadhani; Chelsea Andreana Natasha; Ali Akbar (Indo Publishing, 2025)
Social justice is one of the core principles in Islamic teachings, serving as the foundation for the creation of a harmonious and civilized society. The Qur’an, as the primary source of Islamic law and ethics, frequently emphasizes the importance of justice in various aspects of life, including law, economy, and social relations. Justice in the Qur’anic perspective extends beyond legal fairness; it encompasses moral, spiritual, and humanitarian dimensions rooted in the unity of God (tawḥīd). This study aims to examine the concept of social justice from the Qur’anic perspective by analyzing verses that discuss the principles of justice and their implementation in modern society. The research employs a qualitative descriptive approach with a thematic analysis of relevant Qur’anic verses and interpretations from both classical and modern exegeses.Through this method, the study seeks to uncover the comprehensive meaning of justice within both theological and social dimensions.The findings indicate that the Qur’an regards justice as a central pillar in establishing social order. The Qur’anic conception of social justice encompasses equality, social responsibility, and the protection of human rights without discrimination.These principles are highly relevant to the modern world, which continues to face inequality and structural injustice. Therefore, the application of Qur’anic justice values can serve as a moral and ethical framework for creating a fair, prosperous, and compassionate society.